STRATEGI PEMASARAN INDIBIZ TELKOM SURABAYA UTARA - Yaqin, Ainul; Utomo, Priyo; Zaman, Komarun (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The number of Indibiz provider users has a greater number than other providers even though the subscription price that must be paid is more expensive than other providers. In this study, researchers used qualitative methods, while the type of research method used in this study was descriptive method. PT. Telkom Indonesia Tbk has a great opportunity to target its target. But in this case the company must really understand the needs of consumers regarding the smoothness of their communication. The continuity and fluency of their digital communication to get fast information must be realized with the support of new products offered by PT. Telkom Indonesia. Indibiz Marketing Strategy has an effective and efficient strategy. Based on the indicators in the 4P theory (product, price, place, promotion) that PT Telkom has fulfilled all the existing indicators. On Product Indicators, Indihome has an attractive design. The lack of information provided by agencies regarding their products is a factor for consumer misunderstanding regarding the products they offer, both in terms of price, function, and how to use them. In Indibiz Marketing, PT. Telkom Indonesia, Tbk Surabaya uses several methods, namely door to door selling and personal selling which is done by reaching public housing to provide indibiz products. Customers who want to become Indibiz users can visit the Plasa Indihome office owned by PT. Telkom Indonesia Human resources play a decisive role in the development and number of Indihome subscribers, especially in Surabaya